Enhanced Cr(VI) removal from water using a green synthesized nanocrystalline chlorapatite: Physicochemical interpretations and fixed-bed column mathematical model study. (February 2021) - Han, Xuan; Zhang, Yong; Zheng, Chunmiao; Yu, Xiangnan; Li, Shiyin; Wei, Wei
Abstract: Apatite-based minerals have attracted much attention in the remediation of heavy metal-contaminated environment. However, exploring apatite with efficient adsorption performance for inorganic oxyanions such as Cr(VI) remains a challenge. Herein, a novel nanocrystalline chlorapatite (ClAP) was promptly prepared by a green method using eggshell wastes as calcium source with the purpose to enhance Cr(VI) adsorption capability. The generated ClAP was characterized by XRD, SEM-EPMA, TEM, FTIR, and BET analyses. Batch and column experiments were subsequently carried out to explore the influencing factors, adsorption capacity and removal mechanism. Results showed that ClAP exhibited excellent stability and adsorption performance for Cr(VI) (63.47 mg g −1 ), which was much greater than that of hydroxyapatite and most reported materials. The adsorption process was fitted well by the pseudo-second-order model and the Langmuir model. In fixed bed column experiments, a novel time-fractional derivative model exhibited much better suitability in interpreting the observed breakthrough curves of Cr(VI) than traditional models. Furthermore, the reusability of ClAP in column was evaluated. Results showed that the adsorption capacity maintained well after consecutively reused for five cycles. Studies of the effect of pH, as well as FTIR and XPS investigations indicated that Cr(VI) adsorption was mainly ascribed to electrostatic interactions and surface complexation, while the reduction of Cr(VI) to the low-toxicity Cr(III) also existed in the adsorption process. The ClAP adsorbent was also successfully used for Cr(VI) remediation from real wastewater. Hence, nanocrystalline ClAP can be a promising material for enhancing the elimination of oxyanion contaminants such as Cr(VI) from water. Graphical abstract: Image 1 Highlights: ClAP can be synthesized by a green method using eggshells as the calcium source. ClAP has much higher adsorption ability to Cr(VI) than HAP and other adsorbents. Nanocrystalline ClAP exhibits good stability and reusability. Cr(VI) BTCs can be well quantified by a novel time-fractional derivative model.